Outside looking in [large type] : adventures of an observer - Wills, Garry, 1934- (Thorndike Press, 2010)
Bookish and retiring, Garry Wills has been an outsider in the academy, in journalism, even in his church. Yet these qualities have paradoxically prompted others to share intimate insights with him - perhaps because he is not a rival, a competitor, or a threat. As an observer, he has been able to look in on extraordinary and unlikely places and events. Outside Looking In is a compelling chronicle of an original thinker at work in remarkable times.